ADVERTISING AVOIDANCE PADA IKLAN DI MEDIA TELEVISI - Indah Dwi Pratama; Ujang Sumarwan; Hari Wijayanto (School of Business, Bogor Agricultural University (SB-IPB), 2016)
One factor that can interfere with the absorption rate of viewers on television advertisement is advertising avoidance which shows the difference between the number of viewers who watch advertisement programs and the number of viewers who watch television programs. The factors that affect advertising avoidance include the demography of the viewers (gender, age, area of residence, and social economic status, or SES), advertising attributes (the television stations, order of ads, genre of the program, and advertising sector), and competition (DayPart). The study attempted to measure the level of advertising avoidance in Indonesia and its relation to various factors that influence it by using the secondary data generated by Nielsen Audience Measurement Indonesia through Television Audience Measurement (TAM). The methods utilized consisted of the t-test independent sample, one way ANOVA, Tukey, Kruskal Wallis, and Dunn Bonferoni. The result showed that the level of advertising avoidance in Indonesia reached by 23%, with relatively similar results to the other studies in various countries. The hypothesis test results also showed a significant relationship between the advertising avoidance and demographic variables, advertising attributes, and competitions affecting this avoidance. On one hand, the findings of the study are expected to be useful for the advertisers to plan their advertisements on television so that they become more effective and efficient. On the other hand, television stations can utilize these findings as a development strategy to expand their audience segmentation and to accommodate the needs of the advertisers more optimally.Keywords: advertising avoidance, television advertisement, TAM, ANOVA, Tukey